Interactive mandarin chinese (Berlitz Publishing, 2008)
Berlitz beginner audio course --Mandarin Chinese guaranteed (c2008), and the Berlitz Word Traveler game (c2004-2009). "Tools available to help you learn Mandarin Chinese at your own pace." Bonus: CD-ROM includes access to 6 other languages. Learn numbers, dates, basic words, dialogs, and play language-learning games.